Réponses

  • Utilisateur Brainly
2014-05-02T07:59:38+02:00
2+3x=7-3x
6x=5
x=5/6

5,1-x=-8x+1,7
7x=6,8
x=6,8/7
x=34/35

7x-(5x+3)=5(x-3)+2
-3x=-10
x=10/3

7(x+2)-3=25-(3x+4)

10x=10
x=1
2014-05-02T08:40:46+02:00
Salut :)

2 + 3x = 7 - 3x 
3x = 5 - 3x
6x = 5
x = 5/6


5,1 - x = -8x + 1,7 
5.1 + 7x = 1.7
7x = -3.4
x = -3.4/7

7x - (5x + 3) = 5(x - 3) + 2 
7x - 5x - 3 = 5x - 15 + 2
2x - 3 = 5x - 13
-3x - 3 = - 13
-10 = -3x
x = 10/3

7(x + 2) - 3 = 25 - (3x + 4)
7x + 14 - 3 = 25 - 3x - 4
7x + 11 = -3x + 21
10x + 11 = 21
10x = 10
x = 10/10
x = 1

J'espère t'avoir aidé(e) ! :)